The Influence of Profit Sharing and Brand Image On Customer Saving Decisions In Bmt Nu Banyuwangi Area - Jazil, Ahmad Syafi’ul; Is'adi, Munir; Ahmadiono (Dinasti International Journal of Economics, Finance & Accounting, 2024)
Research focus: 1. Knowing the partial influence of profit sharing on customers' decisions to save in Bmt Nu Area South Banyuwangi 2. Knowing the partial influence of brand image on customers' decisions to save in Bmt Nu Area South Banyuwangi. 3. Knowing the simultaneous influence of profit sharing and brand image on customers' savings decisions in Bmt Nu Area South Banyuwangi. This research is in the form of quantitative research and this research can be classified as explanatory research, so this research uses a sampling technique using purosive sampling with a total of 120 respondents.Based on the results of testing the hypothesis of this research on the profit sharing variable in saving decisions, the results show that partial and simultaneous profit sharing has a positive and significant effect on saving decisions.